Optimisation of technological processes in terminals - Jarašūniene, Aldona (Transport, 2004)
In this article technological processes in transport terminals are analysed. A technological scheme of the transport terminal is analysed graphically reflecting the sequence of working operations with regard to aerial location, necessary equipment, outfit and workers. A technological graph chart reflecting the technological acceptability and time normatives of technological operations of a transport process is present. The estimation and adaption of models in transport terminals are presented. A dynamic model serving the development of general transport capacities was elaboated for process modeling of transport terminals.First Published Online: 27 Oct 2010